Perspectives on gender and the division of labor: readings on the experience of migrant families in Santiago, Chile - Grau Rengifo, María Olaya; Cárdenas Sánchez, María Elvira (Critical Proposals in Social Work, 2023)
This article seeks to know how migrant mothers who reside in Santiago de Chile and who have children under 5 years of age have lived, their gender roles in the exercise of parenting and care from their migratory experience. To this end, interviews were conducted with 17 migrant mothers of Latin American origin who participate in the Chile Crece Contigo System from Family Health Centers in Santiago communes. Results show that they associate parenting and care tasks with a naturalized role, in which they identify themselves and at the family level as the main responsible for these tasks. In this way, their migratory experience is deeply related to the need to guarantee the care and well-being of their children as the main axis, which transforms or maintains gender roles throughout their migratory experience, and is related to studies on maternity and mental health of migrant women where the sexual division of labor and the overload of child-rearing and care work on women emerge. This raises challenges that can be addressed by the State, the ChCC and academia.